Hermite-Hadamard and Schur-Type Inequalities for Strongly h-Convex Fuzzy Interval Valued Functions - Yang, Putian; Zhang, Shiqing (Journal of function spaces, 2022)
The concept of fuzzy theory was developed in 1965 and becomes an acknowledged research subject in both pure and applied mathematics and statistics, showing how this theory is highly applicable and productive in many applications. In the present study, we introduced the definition of fuzzy interval valued strongly h-convex function and investigated some of its properties. We established Hermite-Hadamard and Schur-type inequalities for the class of fuzzy interval valued strongly h-convex function.